COMPARATIVE STYLISTIC ANALYSIS OF SELECTED BAETA'S RINCONADA POEM AND ITS ENGLISH TRANSLATION - Fajardo, Dan Fereth; Oliveros, Nemuel; Ibarbia, Julia Ledah; Derecho, Desiree; Pesebre, Rhea (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study applies a stylistic analysis, building on the paradigm established by Latif, Ajmal, and Maqbool (2022), to examine Elbert Baeta's Rinconada poem